WANITA TANGGUH DALAM NOVEL IBUK KARYA IWAN SETYAWAN - Juliarta, I Gusti Bagus (Humanis; Volume 6. No. 3. Maret 2014, 2014)
Object of this study is novel Ibuk written by Iwan Setyawan. The reasont Ibuk chosen as object of the study are as follow: (1) Ibuk (Tinah) physically strong, (2) background not complete primary education Ibuk (Tinah) figure makes a bolt, resolute, and straght forwad to be able to send their fives children, (3) Ibuk (Tinah) figure has the soul of leadership and responsibility in the family. Based on the above reasons, it can be concluded Ibuk a strong female figuare in the struggle of life for family. Thus analysis of the psychology and personality psychology literature is very appropriate to be used to analyze the main character in the story.
Keywords: literary psychology, personality psychology, and resilient.